Neither repetition duration nor number of muscle actions affect strength increases, body composition, muscle size, or fasted blood glucose in trained males and females - Carlson, L.; Jonker, B.; Westcott, W. L.; Steele, J.; Fisher, J. P. (Applied Physiology, Nutrition, and Metabolism, 2019)
A key variable within resistance training (RT) is that of repetition duration: the time (seconds) taken to perform the concentric and eccentric muscle actions of a repetition. Research has produced equivocal results with regard to strength and muscle mass increases; many studies have created parity in the number of repetitions, but there has been disparity in the load used and the time under load (TUL). The purpose of this study was to compare load- and TUL-matched groups performing resistance exercise using different repetition durations. Fifty-nine male and female participants were randomized into 3 groups: 2s:4s (n = 18), 10s:10s (n = 20), or a group that performed 30 s of eccentric, 30 s of concentric, and 30 s of eccentric muscle actions (e.g., 1.5 repetitions; n = 21). Participants were supervised in one-on-one RT sessions 2 days/week for 10 weeks. Outcomes were 10 repetitions maximum (RM) and predicted 1RM for chest press, leg press, and pulldown exercises, as well as body composition, upper arm and thigh muscle mass, and fasted blood glucose. Analyses revealed significant increases in strength for all exercises but no between-group differences and no statistically significant time course changes for the other variables. Repetition duration does not affect the increases in strength in trained participants when exercise is performed to momentary failure. Because time constraints and perceived difficulty are often cited as barriers to exercise, it is important to recognize that the low-volume (single-set), machine-based protocol employed herein produced worthwhile strength increases in trained participants.